A genetics-based approach confirms immune associations with life history across multiple populations of an aquatic vertebrate (Gasterosteus aculeatus) - Whiting, James R.; Magalhaes, Isabel S.; Singkam, Abdul R.; Robertson, Shaun; D'Agostino, Daniele; Bradley, Janette E.; MacColl, Andrew D.C. (Wiley, 2018)
Understanding how wild immune variation covaries with other traits can reveal how costs and trade‐offs shape immune evolution in the wild. Divergent life history strategies may increase or alleviate immune costs, helping shape immune variation in a consistent, testable way. Contrasting hypotheses suggest that shorter life histories may alleviate costs by offsetting them against increased mortality, or increase the effect of costs if immune responses are traded off against development or reproduction. We investigated the evolutionary relationship between life history and immune responses within an island radiation of three‐spined stickleback, with discrete populations of varying life histories and parasitism. We sampled two short‐lived, two long‐lived and an anadromous population using qPCR to quantify current immune profile and RAD‐seq data to study the distribution of immune variants within our assay genes and across the genome. Short‐lived populations exhibited significantly increased expression of all assay genes, which was accompanied by a strong association with population‐level variation in local alleles and divergence in a gene that may be involved in complement pathways. In addition, divergence around the eda gene in anadromous fish is likely associated with increased inflammation. A wider analysis of 15 populations across the island revealed that immune genes across the genome show evidence of having diverged alongside life history strategies. Parasitism and reproductive investment were also important sources of variation for expression, highlighting the caution required when assaying immune responses in the wild. These results provide strong, gene‐based support for current hypotheses linking life history and immune variation across multiple populations of a vertebrate model.